2021
DOI: 10.3390/su132011244
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Feminist Agroecology

Abstract: Agroecology is gaining ground as a movement, science, and set of practices designed to advance a food systems transformation which subverts the patterns of farmer exploitation currently entrenched in dominant agricultural models. In order for agroecology to achieve its espoused twin aims of social and ecological wellbeing, women and other historically marginalized stakeholders must be empowered and centered as the movement’s protagonists. The importance of gender and social considerations is not limited to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The result showed that women were more likely to join the group than their main counterparts. This confirms the idea that agroecology groups provide an empowerment platform for women and other historically marginalized stakeholders in the food system such as the caste and smallholder farmers (Oteros-Rozas et al, 2019;Zaremba et al, 2021). This is also not surprising as 83% of the group members were women.…”
Section: Determinants For Joining the Groupsupporting
confidence: 71%
“…The result showed that women were more likely to join the group than their main counterparts. This confirms the idea that agroecology groups provide an empowerment platform for women and other historically marginalized stakeholders in the food system such as the caste and smallholder farmers (Oteros-Rozas et al, 2019;Zaremba et al, 2021). This is also not surprising as 83% of the group members were women.…”
Section: Determinants For Joining the Groupsupporting
confidence: 71%
“…This method creates awareness about women's power, promotes their participation in social decision-making, educates women on different types of technologies and helps them become agents of change. The second one is the policy approach that promotes women's empowerment policies [52]; (2) enhancement of farmers' independence; fairness, participation in land and natural resource governance; and (3) the privileging of the value of diversity in knowledge and know-how [41,49]. Thus, agroecology hinges on collaborative participation of researchers and knowledge systems, allowing decolonization of research and the identification of norms for governing ecosystems and improving agriculture systems [53].…”
Section: Agroecology As An Integrated and Interdisciplinary Approachmentioning
confidence: 99%
“…Overuse of nitrogen fertilization in China's largely agriculturalized areas has resulted in major environmental issues, including air, soil, and water enrichment with reactive nitrogen from agricultural sources. The study outlined in [18] examines grain yields and nitrogen loss patterns in two intensive double-cropping systems in China: waterlogged rice/upland wheat in the Taihu region and rainfed maize and irrigated wheat on the North China Plain. Current nitrogen application approaches, averaging 550-600 kg per hectare every year, do not result in appreciable gains in crop yields, in contrast to optimal nitrogen fertilization methods that have the potential to save 30-60% of nitrogen usage.…”
Section: Sustainable Intensificationmentioning
confidence: 99%